Plan de Desarrollo con énfasis en la Economía Popular y Solidaria: Herramientas para el Fortalecimiento de la Gestión de la Calidad de Vida de la Comunidad San Francisco - Zárate Ganan, Jorge Luis (2023)
ABSTRACT: The socioeconomic, local, or sustainable development of a territory is not an end, but a constant process of construction, in this thought several government agencies, nonprofit, private have contributed partially with strategies, policies towards marginalized societies especially in the rural sector. In this scenario, a social and solidarity economy recognized in Ecuador since 2008, allows its actors, associations, cooperatives and in this case study a community organization, to set goals, strategies, practice their principles and improve their quality of life. This research project consists of the proposal of a development plan for the improvement of the quality of life, with emphasis on the social and solidarity economy, for the inhabitants of the San Antonio community of the Achupallas parish, Alausi canton, based on a situational diagnosis of the area, through the application of a mixed methodology of descriptive and correlative type, The use of the tools are socialized and validated with the community's stakeholders. The programs and projects cover the period from 2023 to 2028. The results of the diagnosis show several problems and levels of poverty, as well as the potential of the territory, which should be exploited with acts of solidarity practiced by its inhabitants, this experience of solidarity, reciprocal, complementary work, allows the strategies, objectives, programs and projects proposed to be prioritized, empowered, by the participation in the construction of the plan of its actors, the community. Key words: development plan, popular and solidarity economy, community, territorial planning, local development, quality of life.